Sumatera Thawalib dan Ide Pembaharuan Islam di Minangkabau (1918-1930) - Abbas, Afifi Fauzi; Afifi, Abdullah A (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2022)
The idea of reforming Islamic education has developed massively in 1918-1930 in Minangkabau. The role of Sumatra Thawalib in comprehensively renewing Islam has provided a major breakthrough in solving socio-political, economic and social issues. Sumatra Thawalib's significant role was born from its main role in the education sector. Even further, Sumatra Thawalib has provided a treasure trove of Islamic renewal ideas that rely on the purification movement which also provides wide space for the opening of constructive ijtihad doors that impress on social civilization. This article was written so that discussions about Sumatra Thawalib can continue to be enriched so that we can get various points of view and alternative narratives. Limited references are also a serious challenge in compiling this article.